Through the supply chains it may not transmit? A case of monetary policy bottlenecks - Boissay, Frédéric; Garcia-Appendini, Emilia; Ongena, Steven (Journal of Financial Intermediation, 2026)
We investigate the transmission of monetary policy through the supply chains with US data on corporate linkages. Our analysis uncovers three key insights. First, contractionary monetary conditions lead to production disruptions in financially constrained rms. Second, these disruptions extend to the suppliers and customers of such firms. Third, disruptions intensify when financially constrained firms purchase or sell specialized goods. These findings suggest that monetary tightening creates bottlenecks in supply chains, forcing firms to curtail production when they cannot substitute their constrained business partners. \ Monetary policy bottlenecks" amplify the impact ofmonetary policy beyond the standard balance sheet channel of transmission.